Designing Games With A Purpose. - Von Ahn, Luis; Dabbish, Laura (Communications of the ACM, 2008)
The article discusses design principles for "games with a purpose (GWAP)." As a side effect of playing a GWAP, participants accomplish tasks that computers themselves cannot. An example would be the ESP Game from Google, in which players attach labels to images. Noting the appeal of GWAP as ever-increasing numbers gain Internet access, the authors discuss how problems not easily solved by machines can be addressed by GWAP. Output-agreement games, input-agreement games, and inversion-problem games are all discussed, as well as ways of making the games more enjoyable for users.